On Research in Action and Action in Research - Bodil Stilling Blichfeldt; Jesper Rank Andersen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2005)
A unique (and challenging) characteristic of social sciences is that these sci-ences are multi-paradigmatic and adhere to a wide range of research strategies. One research strategy that social scientists can choose to rely on is action re-search. However, action research qualifies as a research strategy much criticised for not being subject to scientific rigor. Drawing on an extensive review of the literature on action research, this paper discusses what action research is (not) and what it can (not) do for social scientists, who wish to do research of rele-vance to practitioners. Especially, this paper discusses lines of criticism that ac-tion research is subject to and further, it suggests ways in which action re-searchers may enhance quality of action research. In particular, we argue that enhancement of quality of action research is necessary if we wish for communi-ties of social scientists to acknowledge action research as a scientific endeavour as well as if we wish for such communities to rely on the findings of action re-search studies.
Keywords: 330